Omental Macrophagic “Crown-like Structures” Are Associated with Poor Prognosis in Advanced-Stage Serous Ovarian Cancer - Liang, Yu-Ling; Lin, Chang-Ni; Tsai, Hsing-Fen; Wu, Pei-Ying; Lin, Sheng-Hsiang; Hong, Tse-Ming; Hsu, Keng-Fu (Current oncology (Toronto), 2021)
The tumor microenvironment is a well-recognized framework in which immune cells present in the tumor microenvironment promote or inhibit cancer formation and development. A crown-like structure (CLS) has been reported as a dying or dead adipocyte surrounded by a ‘crown’ of macrophages within adipose tissue, which is a histologic hallmark of the inflammatory process in this tissue. CLSs have also been found to be related to formation, progression and prognosis of some types of cancer. However, the presence of CLSs in the omentum of advanced-stage high-grade serous ovarian carcinoma (HGSOC) has not been thoroughly investigated. By using CD68, a pan-macrophage marker, and CD163, an M2-like polarization macrophage marker, immunohistochemistry (IHC) was performed to identify tumor-associated macrophages (TAMs) and CLSs. This retrospective study analyzed 116 patients with advanced-stage HGSOC who received complete treatment and had available clinical data from July 2008 through December 2016 at National Cheng Kung University Hospital (NCKUH) (Tainan, Taiwan). Based on multivariate Cox regression analysis, patients with omental CD68+ CLSs had poor OS (median survival: 24 vs. 38 months, p = 0.001, hazard ratio (HR): 2.26, 95% confidence interval (CI): 1.41–3.61); patients with omental CD163+ CLSs also had poor OS (median survival: 22 vs. 36 months, HR: 2.14, 95%CI: 1.33–3.44, p = 0.002). Additionally, patients with omental CD68+ or CD163+ CLSs showed poor PFS (median survival: 11 vs. 15 months, HR: 2.28, 95%CI: 1.43–3.64, p = 0.001; median survival: 11 vs. 15 months, HR: 2.17, 95%CI: 1.35–3.47, respectively, p = 0.001). Conversely, the density of CD68+ or CD163+ TAMs in ovarian tumors was not associated with patient prognosis in advanced-stage HGSOC in our cohort. In conclusion, we, for the first time, demonstrate that the presence of omental CLSs is associated with poor prognosis in advanced-stage HGSOC.